Type I interferons are not critical for skin allograft rejection or the generation of donor-specific CD8(+) memory T cells - Oberbarnscheidt, Martin H. (2009)
Type I interferons (IFN-I) link innate to adaptive immunity in microbial infection, autoimmune disease, and tumor immunity. It is not known whether IFN-I have an equally central role in alloimmunity. Here we tested this possibility by studying skin allograft survival and donor-specific CD8(+) T cell responses in mice that lack the IFN-I receptor (IFN-IR(−/−)). We found that IFN-IR(−/−)mice reject fully allogeneic wildtype skin grafts at the same rate as wildtype recipients. Similarly, allograft rejection was not delayed if IFN-IR(−/−) male skin was transplanted to syngeneic IFN-IR(−/−) female mice. Quantitation of the male (H-Y)-specific CD8(+) T cell response in these mice revealed normal generation of donor-specific CD8(+) effector T cells but four-fold reduction in CD8+ memory T cells. Memory CD8(+) T cells generated in the absence of IFN-IR had normal phenotype and recall function, assessed by ex vivo cytokine production and the ability of IFN-IR(−/−) mice to mount second set rejection. Finally, these memory T cells were maintained at a constant number despite their inability to respond to IFN-1. Our findings indicate that IFN-I cytokines are not critical for acute allograft rejection or for the expansion and differentiation of donor-specific CD8(+) T cells into long-lived, functional memory T cells.